BIOTECHNOLOGY DEEP MINERALIZATION DEPOSITS OF CITY WASTE WATER CONTAINING HEAVY METAL IONS - and (Municipal economy of cities. Series: «Economy science», 2013)
The directions of research sludge treatment of urban waste water associated with the deepening of the mineralization of the organic matter, developed requirements for a new processing technology and experimental studies. Experimental results have shown high efficiency salinity greatly simplifies the separation of heavy metals.